Habitat suitability estimated by niche models is largely unrelated to species abundance. Issue 12 (25th September 2018) - Dallas, Tad A.; Hastings, Alan
Abstract: Aim: Data on species occurrences are far more common than data on species abundances. However, a central goal of large‐scale ecology is to understand the spatial distribution of abundance. It has been proposed that species distribution models trained on species occurrence records may capture variation in species abundance. Here, we gauge support for relationships between species abundance and predicted climatic suitability from species distribution models, and relate the slope of this relationship to species traits, evolutionary relationships and sampling completeness. Location: USA. Time period: 1658–2017. Major taxa studied: Mammal and tree species. Methods, Results: To explore the generality of abundance–suitability relationships, we trained species distribution models on species occurrence and species abundance data for 246 mammal species and 158 tree species, and related model‐predicted occurrence probabilities to population abundance predictions. Further, we related the resulting abundance–suitability relationship coefficients to species traits, geographic range sizes, evolutionary relationships and the number of occurrence records to investigate a potential trait or sampling basis for abundance–suitability relationship detectability. We found little evidence for consistent abundance–suitability relationships in mammal ( r ¯ = .045) or tree ( r ¯ = −.005) species, finding nearly as many negative and positive relationships. These relationships had little explanatory power, and coefficients were unrelated to species traits, range size or evolutionary relationships. Main conclusions: Our findings suggest that species climatic suitability based on occurrence data may not be reflected in species abundances, suggesting a need to investigate nonclimatic sources of species abundance variation.